Silicon-mediated modulation of maize growth, metabolic responses, and antioxidant mechanisms under saline conditions - Muhammad Saad Ullah; Athar Mahmood; Hussam F. Najeeb Alawadi; Mahmoud F. Seleiman; Bilal Ahmad Khan; Muhammad Mansoor Javaid; Abdul Wahid; Fnu Abdullah; Daniel O. Wasonga (BMC Plant Biology)
Abstract Purpose This study explored how exogenous silicon (Si) affects growth and salt resistance in maize. Methods The maize was cultivated in sand-filled pots, incorporating varied silicon and salt stress (NaCl) treatments. Silicon was applied at 0, 2, 4, 6, and 8 mM, and salt stress was induced using 0, 60 and120 mM concentrations. Soil salinity triggers a range of physiochemical abnormalities, often leading to growth arrest and, eventually, the demise of susceptible plants. Results The salt stress significantly reduced the total chlorophyll content (12.58–33.14%), antioxidant enzymes, notably SOD (32–46%), POD (10.33–18.48%), and CAT (10.05–13.19%). In contrast, salt stress increased secondary metabolites, including total phenols (49.11–66.35%.), flavonoids (220.99–280.36%), and anthocyanin (50.04–58.6%). Adding silicon under salt stress reduced the absorption of Na+ by 6.69%, 20.7%, 41.12%, and 34.28%, respectively, compared to their respective controls. Additionally, applying Si at 8 mM significantly enhanced antioxidant enzymes such as SOD (50.57%), POD (15.58%), CAT (10.06%) and chlorophyll ratio (21.32%). Conclusion Silicon application positively impacted nearly all growth and physiological features, indicating it helps mitigate against salinity. This was achieved by regulating various salinity indicators, where secondary metabolites, including anthocyanin, ascorbic acid, total phenols, and flavonoids, increased. Graphical Abstract